A randomised controlled trial of fibrinogen concentrate during scoliosis surgery. (4th June 2020) - Chen, W.; Shen, J.; Zhang, Y.; Hu, A.; Liang, J.; Ma, L.; Yu, X.; Huang, Y.
Summary: Bleeding and blood transfusion are common after scoliosis surgery. Fibrinogen is essential for blood clot formation and depletes quickly during haemorrhage. We randomly allocated 102 children 12–18 years old having surgery for idiopathic scoliosis, 51 to intra‐operative fibrinogen concentrate 30 mg.kg −1 (maximum 2 g) and 51 to saline placebo. Fibrinogen reduced peri‐operative blood loss by a median (95%CI) volume of 155 (5–320) ml, from a median (IQR [range]) of 1035 (818–1420 [400–3030]) ml to 885 (755–1155 [270–2645]) ml, p = 0.04. Seven and four children received allogeneic red blood cell transfusion after fibrinogen and placebo, respectively, p = 0.34. There were no side‐effects.